Learning Model for Female Students of Dual Role in Facing Academic Procrastination: Evidence in State Islamic University - Muhammad Fadhil; Ali Anhar SyiÔÇÖbul Huda; Daflaini Daflaini; Yatti Fidya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This article aims to find out, analyse, and offer a time management model for female students in the midst of dual roles in dealing with academic procrastination at the Islamic State University. Procrastination is an academic term used for students who delay doing coursework. The act of procrastination can be seen from the delay in completing studies, the inability to manage time, and the inability to manage oneself. This research uses qualitative research methods which are field research. There are two data sources that are the reference for this research. The first is primary data which is key data in the form of interview results. Second, secondary data obtained from research results in the form of scientific articles, books, and other library materials related to the research topic. The data collection techniques used are interviews and documentation. The data analysis techniques used are data condensation, data presentation, and conclusion drawing. This study found that the learning model for dual-role female students in dealing with academic procrastination with proportional time management is very important to be implemented as an effort to avoid procrastination of academic tasks. Female students as self-controllers must have the strength to keep procrastination behaviour away in order to be able to complete academic tasks in a timely manner. The ability of self-control will have a positive effect on the realisation of a balanced academic atmosphere.